Young adult longitudinal patterns of marijuana use among US National samples of 12th grade frequent marijuana users: a repeated‐measures latent class analysis - Terry‐McElrath, Yvonne M.; O'Malley, Patrick M.; Johnston, Lloyd D.; Schulenberg, John E. (Addiction (Abingdon, England), 2019)
Background and Aims Long‐term frequent marijuana use is associated with significant negative outcomes, yet little is known about the longitudinal course of marijuana use among those who start frequent use during adolescence. Objectives are (a) to identify latent patterns of within‐person marijuana use from ages 19–30 years among 12th graders reporting frequent marijuana use, (b) to examine if membership in identified patterns has changed across historical time and (c) to examine if key covariates differentiate class membership. Design, Setting, Participants Longitudinal, national US panel data from 4423 individuals [53.4% of the eligible sample; 2744 (62%) males] who reported frequent marijuana use in 12th grade (modal age 18 years; senior year cohorts 1976–2006) followed biennially from ages 19/20 to 29/30. Measurements Self‐reported past 30‐day marijuana use (frequent use defined as use on 20+ occasions), demographics, college graduation, marriage and parenthood. Findings Repeated‐measures latent class analysis (RMLCA) identified five latent classes of past 30‐day marijuana use from ages 19/20 to 29/30: continued frequent users (estimated membership 23.4%); frequent to non‐frequent users (15.5%); consistent non‐frequent users (18.4%); non‐frequent users to discontinuers (19.5%); and discontinuers (23.2%). In multivariable models, membership in the highest‐risk latent class (continued frequent users) versus one or more of the lower‐risk latent classes was more likely for recent cohorts (P = 0.038 to <0.001), as well as those who did not marry (P = 0.039 to < 0.001) or become parents (P = 0.001) by modal age 29/30. Conclusions Nearly one in four 12th grade (modal age 18 years) frequent marijuana users in the US continues to report high frequency use to age 30; the proportion continuing high frequency use across young adulthood has increased among more recent cohorts.